Hubungan Tingkat Pengetahuan Ibu tentang Cuci Tangan Pakai Sabun dengan Kejadian Diare di Wilayah Kerja Puskesmas Andalas Kota Padang - Mayang Mei Gusri; Tisnawati Tisnawati; Metri Lidya; Indri Ramadini; Verra Widhi Astuti (Jurnal Sehat Mandiri, 2024)
Diarrhea in children can lead to dehydration, hypovolemic shock, hypokalemia, seizures, malnutrition, and even death. The role of mothers in preventing diarrhea is crucial and depends on their knowledge of handwashing with soap (HWWS), as this knowledge is an important factor. This study aims to investigate the relationship between mothers' knowledge of HWWS and the incidence of diarrhea in toddlers in the working area of the Andalas Health Center in Padang City. This observational analytic study employs a cross-sectional design, with data collection conducted from September 2023 to May 2024. The study population consists of 438 mothers who bring their children to the KIA outpatient clinic, with a sample of 88 participants selected using accidental sampling. Data was collected through questionnaires and processed via editing, coding, entry, cleaning, and tabulation. Analysis utilized the Chi-square test (CI 95%). Preliminary results showed that 58 toddlers (65.9%) had diarrhea without dehydration, and a majority of mothers (53.4%) exhibited poor knowledge. A significant relationship was found between mothers' knowledge of HWWS and diarrhea incidence, with a p-value of (0.000). The conclusion is that higher levels of knowledge about HWWS are associated with a lower incidence of diarrhea in toddlers. Ongoing health education and outreach programs are recommended to improve community knowledge of HWWS.